Odpowiedzi

Najlepsza Odpowiedź!
2009-12-03T16:44:50+01:00
5x-1=44
5x=45
x=9

3x+5=26
3x=21
x=7

-2x-2/3=5 1/3
-2x=6
x=-3

0,6y+ 4/5=12,8
0,6y=13,6
y=68/3

2/3 x-8=7
2/3x=15 |*3
2x=45
x= 22,5
2 5 2
2009-12-03T16:44:43+01:00
5x-1=44 |+1
5x=45 | /5
x=9

3x+5=26 |-5
3x=21 | /3
x=7

-2x-2/3=5 1/3 |+2/3
-2x=6 |/(-2)
x=-3

0,6y+ 4/5=12,8 |-4/5
0,6y=12 |/0,6
y=12*5/3
y=20

2/3 x-8=7 |+8
2/3x=15 |*3/2
x=45/2

1 5 1
2009-12-03T16:48:24+01:00
5x-1=44 /+1
5x=45 //5
x=9

3x+5=26 /-5
3x=21 /3
x=7

-2x-2/3=5 1/3 /+2/3
-2x=6 /-2
x=-3

0,6y+ 4/5=12,8
0,6y+0,8=12,8 /-0,8
0,6y=12 /0,6
y=20

2/3 x-8=7 /+8
2/3x=15 /2/3
x=22,5
1 5 1